Melacak Ideal Moral dalam Hadis La Yakhtubu al-Rajulu â€˜Ala Khitbati Akhihi: Sebuah Telaah Ilmu Hadis - Salam, Nor (De Jure: Jurnal Hukum dan Syari'ah, 2016)
Hadith (the Prophet tradition) is the source of law which occupies a central position after the Quran which serves as explanatory of the contents of the Quran. However, if the Quran has been ascertained to be qat'i both sides wurud or tsubutnya, not the case with a Hadith that still raises various problems both in the assessment of the sanad authenticity and the contains. Thus, it is not all hadith have authentic quality both the sanad nor the matan, so it is needed to do research. Another issue is no less complex in order to "unearth" the values contained in a hadith tradition of honor in the present context as the traditions in the realm ahwal syakhsiyah one of them is the hadith about khitbah. In this study, the hadith about khitbah narrated by Imam Abu Daud derived from lines Ahmad ibn Amr ibn Sarh witheditorial worth is valid both in terms of sanad and matannya, while its values ranged at the level of the juridical and ethical. In the juridical level, the hadith indicates the prohibition of making a proposal to the proposal of others, whereas the level of ethics or mysticism, the tradition is more referring to the creation of a harmonious life.Hadis nabi adalah sumber hukum yang menempati posisi sentral setelah al-Quran yang berfungsi sebagai penjelas terhadap kandungan al-Quran. Namun demikian, jika al-Quran sudah dipastikan bersifat qatâ€™i baik dari sisi wurud maupun tsubutnya, tidak demikian halnya dengan hadis nabi yang masih menimbulkan aneka persolan baik dalam penilain terhadap otentisitas sanad maupun matannya. Dengan demikian, maka tidaklah semua hadis yang disandarkan kepada nabi berkualitas sahih dari sisi sanad maupun matannya sehingga diperlukan adanya penelitian. Persoalan lain yang tidak kalah rumitnya adalah dalam rangka â€œmembumikanâ€ nilai-nilai yang dikandung dalam sebuah matan hadis dalam konteks kekinian seperti hadis-hadis dalam ranah ahwal syakhsiyah termasuk salah satunya adalah hadis tentang khitbah. Dalam penelitian ini, hadis tentang khitbah yang diriwayatkan oleh imam Abu Daud yang berasal dari jalur Ahmad bin Amr bin Sarh dengan redaksi bernilai sahih baik dari sisi sanad maupun matannya, sedangkan nilai yang dikandungnya berkisar pada tataran yuridis dan etika. Dalam tataran yuridis, hadis tersebut menunjukkan larangan terjadinya peminangan terhadap pinangan orang lain, sedangkan dalam tataran etika atau tasawuf, hadis tersebut lebih mengacu pada terciptanya kehidupan yang harmonis.